Conserving historical identities through architecture: journeying & mediating everyday space - a case study of CHIJMES - Leong, Joseph Jie Sheng (Nanyang Technological University, 2023)
The issue of land scarcity in Singapore is a perpetual one, and while modern innovations in technology since the 80s have allowed for solutions such as land reclamation to become viable alternatives for such a small island-state, the need to replace older buildings in favour of more space efficient and newer ones has nevertheless endured. I therefore find it necessary to investigate the case of adaptive re-use in Singapore's preservation practices, with close attention to CHIJMES, in a bid to understand the tangible and intangible facets of conservation. It is necessary to address certain key questions in my study of CHIJMES: in reusing a building, how does its significance and narrative change? How viable is the practice of adaptive re-use? Finally, is there meaning left in adapted architecture? By the end of this paper, I hope to demonstrate its prolific status as a National Monument and its relevance in the study of the practice of adaptive re-use, in turn advocating for conservation practices that successfully reconcile economic development with heritage conservation.